Re-Assembling Democracy: A Nascent Theory of Nonhuman Political Participation - Ejsing, Mads (Theoria (Pietermaritzburg), 2025)
This article explores the concepts of political participation through the lens of new materialism and critical democratic theory. It argues that the concept of political participation must be expanded beyond rational and reflective actions by human beings in order to better encompass the agency of nonhuman entities. Drawing on the work of Jane Bennett, Bonnie Honig, Noortje Marres, and others, the article offers a new theoretical vocabulary for talking about political participation in ways that transcends human-centric boundaries and can help bring an increased ecological awareness to democratic theory.